Learning Academic Vocabulary Through A Mobile App - Ghoues, Mohammed El Amin (Eddissi Languages Journal, 2023)
Improving learners’ lexical competence through vocabulary instruction has not always been prioritised in ESL/EFL teaching agenda. However, the advent of new technologies has fostered the development of mobile assisted language learning (MALL) and the increase in mobile apps for vocabulary learning. This paper will be focusing on the importance of using a mobile app to teach academic vocabulary. The app offers 10 PhD candidates an online course to improve their academic vocabulary as to prepare for their doctoral entrance exams. The online course, quizzes and the survey were used as instruments. The participants were randomly selected to learn academic vocabulary on self-directed basis for a specified duration. At the end of course, all participants responded to the quizzes and survey. Their results were promising and their feedback indicated positive acceptance and appreciation.